Stress-related psychosocial factors at work, fatigue, and risky driving behavior in bus rapid transport (BRT) drivers (2020)
Introduction There is consistent scientific evidence that professional drivers constitute an occupational group that is highly exposed to work related stressors. Furthermore, several recent studies associate work stress and fatigue with unsafe and counterproductive work behaviors. This study examines the association between stress-related work conditions of Bus Rapid Transport (BRT) drivers and risky driving behaviors; and examines whether fatigue is a mechanism that mediates the association between the two. Method A sample of 524 male Bus Rapid Transit (BRT) operators were drawn from four transport companies in Bogotá, Colombia. The participants answered a survey which included an adapted version of the Driver Behavior Questionnaire (DBQ) for BRT operators, as well as the Effort-Reward Imbalance and Job Content Questionnaires, the Subjective Fatigue subscale of the Checklist Individual Strength (CIS) and the Need for Recovery after Work Scale (NFR). Results Utilizing Structural Equation Models (SEM) it was found that risky driving behaviors in BRT operators could be predicted through job strain, effort-reward imbalance and social support at work. It was also found that fatigue and need for recovery fully mediate the associations between job strain and risky driving, and between social support and risky driving, but not the association between effort/reward imbalance (ERI) and risky driving. Conclusions The results of this study suggest that a) stress related working conditions (Job Strain, Social Support and ERI) are relevant predictors of risky driving in BRT operators, and b) that fatigue is the mechanism which links another kind of stress related to working conditions (job strain and low social support) with risky driving. The mechanism by which ERI increases risky driving in BRT operators remains unexplained. Practical applications This research suggests that in addition to the individual centered stress-reduction occupational programs, fatigue management interventions aimed to changing some working conditions may reduce risky driving behaviors and promote safety in the professional drivers' jobs and on the road.